Bottleneck Analysis of the Mobile Internet Diffusion in Emerging Markets - Jaume Benseny; Benjamin Finley; Heikki Hämmäinen (International Telecommunications Society (ITS), 2016)
According to the ITU, in 2013, only 6% of the population in developing countries had access to broadband Internet. Nevertheless, mobile Internet penetration rates have already exceeded those of fixed telecommunication services and may help in bridging the digital divide. To understand this phenomenon, we model the mobile Internet diffusion process via a system dynamics model that includes user competence, data price, and mobile network capacity as the main contributors to consumer utility and consequently, the main mobile Internet diffusion bottlenecks. The links that connect the system dynamics model variables are evaluated through a linear regression analysis that includes, for the first time, actual mobile capacity measurements from 17 metropolitan areas in emerging markets. The results suggest that market competition and mobile capacity are the main mobile Internet diffusion bottlenecks in emerging markets.
Keywords: 330; Mobile Internet; Emerging Markets; System Dynamics; Mobile Capacity